2018
DOI: 10.1073/pnas.1716479115
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic neurogenesis induced by prenatal antiepileptic drug exposure augments seizure susceptibility in adult mice

Abstract: SignificanceRecent clinical studies suggest that environmental insults, such as valproic acid (VPA) exposure, in utero can have adverse effects on brain function of the offspring in later life, although the underlying mechanisms of these impairments remain poorly understood. By focusing on the property of neural stem/progenitor cells (NS/PCs) residing in the adult hippocampus, we identified the mechanism of increased seizure sensitivity in prenatally VPA-exposed adult mice. Furthermore, we found that voluntary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 59 publications
1
33
0
Order By: Relevance
“…Several studies have demonstrated that fetal and early-life exposure to various chemical substances in mammals can induce adverse effects after maturation (Fox, Grandjean, de Groot, & Paule, 2012;Juliandi et al, 2015;Newbold, Padilla-Banks, Jefferson, & Heindel, 2008;Sakai et al, 2018). In addition, it has been reported that many environmental chemical substances, such as bisphenol A, may cause adverse effects (e.g., abnormal behavior, immune function disorder and decreased fertility) in mammals at low levels of exposure ( Vandenberg et al, 2012).…”
mentioning
confidence: 99%
“…Several studies have demonstrated that fetal and early-life exposure to various chemical substances in mammals can induce adverse effects after maturation (Fox, Grandjean, de Groot, & Paule, 2012;Juliandi et al, 2015;Newbold, Padilla-Banks, Jefferson, & Heindel, 2008;Sakai et al, 2018). In addition, it has been reported that many environmental chemical substances, such as bisphenol A, may cause adverse effects (e.g., abnormal behavior, immune function disorder and decreased fertility) in mammals at low levels of exposure ( Vandenberg et al, 2012).…”
mentioning
confidence: 99%
“…While convulsions occurred at a low rate in both groups (c 2 = 0.75, p>0.3), continuous objectively derived home-cage measures were distinct: VPA-exposed mice displayed a blunted motor recovery and remained more distant from their counterparts ( Fig. 5F), suggesting enhanced seizure severity 51,52 .…”
Section: On Ethograms Of Chronic Vpa Exposurementioning
confidence: 95%
“…It engages, among others, the Wnt1 signaling pathway, a robust ''caudalizing'' factor in the rostrocaudal patterning of CNS (Wiltse, 2005;Jang and Jeong, 2018). Prenatal VPA treatment altered the expression in neural stem/progenitor cells of genes associated with cell migration, including CXC motif chemokine receptor 4 (Cxcr4), leading to the ectopic localization of newborn neurons in the hilus of the hippocampus (Sakai et al, 2018). Importantly, of the 20 genes found to be downregulated in VPA-exposed marmoset neonates, Frizzled3 (FZD3) and PIK3CA have been implicated in the axon guidance signaling pathway required for the normal development of the anterior commissure and corpus callosum (Mimura et al, 2019).…”
Section: Transcriptional Effectsmentioning
confidence: 99%